Introduction to Networking Infrastructure on Cisco Packet Tracer: Routing a Home-to-Home Network to a Central Server - Syahrul Al Habib; Rahmat Fajrial Azim; Muhammad Rizqi Raihan Firdaus; Diana Nur Haliza; Muhammad Izzudin Rosadi; Sitti Nurbaya Ambo; Yana Adharani; Nurvelly Rosanti; Rully Mujiastuti (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Lack of understanding about computer networks and routing configurations poses a challenge for students and the general public interested in technology. To address this, a Webinar and Workshop titled “Introduction to Networking Infrastructure on Cisco Packet Tracer: Routing a Home-to-Home Network to a Central Server” was held. The event aimed to provide theoretical and practical knowledge of computer networks and routing simulations using Cisco Packet Tracer. The Webinar covered basics such as network types, IP addresses, and an introduction to Cisco Packet Tracer, while the Workshop focused on hands-on practice. Evaluation revealed a significant improvement in participants' understanding, with average Pre-Test scores rising from 70% to 90% in the Post-Test. Attended by 40 participants from various institutions, 95% expressed satisfaction with the material and presenter delivery. The activity successfully enhanced participants' knowledge and skills in computer networking.